Inovasi Pelayanan Administrasi Kependudukan Melalui Websit SiLAWO Pada Dinas Kependudukan dan Pencatatan Sipil Kota Dumai - Marlina, Divani Sindi; Khotami (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This study analyzes the innovation in population administration services through the implementation of the SiLAWO website (Online Population Administration Service System) by the Dumai City Department of Population and Civil Registration (Disdukcapil), and identifies the barriers to its implementation. The background of this research is the need for fast, efficient, and technology-based public services in line with bureaucratic reform and the development of e-government. A descriptive qualitative method was used, with data collected through interviews, observations, and documentation involving Disdukcapil officials, SiLAWO administrators, and service users. The findings indicate that SiLAWO facilitates easier access, speeds up administrative processes, and reduces queues. However, challenges such as low digital literacy, limited outreach, poor internet infrastructure in certain areas, and technical system issues remain. This innovation meets key attributes of Rogers' diffusion of innovation theory, such as relative advantage, compatibility, and observability. In conclusion, SiLAWO represents a positive step in digital public service transformation but still requires system improvements, increased digital literacy efforts, and strengthened infrastructure for optimal implementation.